A statement on the developmental immunotoxicity of bisphenol A (BPA): answer to the question from the Dutch Ministry of Health, Welfare and Sport. (13th October 2016) - ,; Silano, Vittorio; Bolognesi, Claudia; Castle, Laurence; Cravedi, Jean‐Pierre; Engel, Karl‐Heinz; Fowler, Paul; Franz, Roland; Grob, Konrad; Gürtler, Rainer; Kärenlampi, Sirpa; Mennes, Wim; et al.
Abstract: This statement addresses a request to EFSA from the Dutch Ministry of Health, Welfare and Sport to assess the impact of recent evidence underlying the conclusions of the 2016 RIVM report on the temporary tolerable daily intake (t‐TDI) for BPA of 4 μg/kg bw per day set by EFSA in 2015. The CEF Panel has then evaluated the results of two studies published by Ménard et al. in 2014, suggesting food intolerance and impaired immune response to parasitic infection in rats exposed perinatally to BPA doses in the μg/kg bw per day range. The same appraisal criteria and weight‐of‐evidence analysis used for the 2015 EFSA opinion on BPA were applied to these studies. This new evidence adds to the indications of immunotoxicity of BPA in animals reported in previous reviews. For the only endpoint for which multiple BPA doses were tested (immunoglobulin G (IgG) levels), a benchmark dose analysis of the dose–response data was carried out. Due to the high interanimal variability within the treatment groups resulting in wide confidence intervals and the limited dose–response, the CEF Panel concluded that these data on anti‐ovalbumin IgG antibodies are not suitable to derive a reference point for BPA on immunotoxicity. Furthermore, the limitations identified in both the Ménard et al. studies confound the interpretation of the results and prevent the assessment of the relevance to human health. The CEF Panel overall considers that the results from the two Ménard et al. studies are not sufficient to call for a revision of the EFSA t‐TDI for BPA. EFSA will start a review of all the scientific evidence published after 2012 and relevant for BPA hazard assessment (including immunotoxicity) in 2017. The results of immunological studies, such as the two evaluated here, would form a useful contribution to this evaluation provided that the limitations identified herein were addressed.